Structure of the merozoite surface protein 1 from Plasmodium falciparum - Dijkman, Patricia M.; Marzluf, Tanja; Zhang, Yingyi; Chang, Shih-Ying Scott; Helm, Dominic; Lanzer, Michael; Bujard, Hermann; Kudryashev, Mikhail (Science advances, 2021)
The merozoite surface protein 1 (MSP-1) is the most abundant protein on the surface of the erythrocyte-invading Plasmodium merozoite, the causative agent of malaria. MSP-1 is essential for merozoite formation, entry into and escape from erythrocytes, and is a promising vaccine candidate. Here, we present monomeric and dimeric structures of full-length MSP-1. MSP-1 adopts an unusual fold with a large central cavity. Its fold includes several coiled-coils and shows structural homology to proteins associated with membrane and cytoskeleton interactions. MSP-1 formed dimers through these domains in a concentration-dependent manner. Dimerization is affected by the presence of the erythrocyte cytoskeleton protein spectrin, which may compete for the dimerization interface. Our work provides structural insights into the possible mode of interaction of MSP-1 with erythrocytes and establishes a framework for future investigations into the role of MSP-1 in Plasmodium infection and immunity. - Structure of the malaria blood-stage parasite’s main surface antigen reveals putative host cell-binding domains. - Structure of the malaria blood-stage parasite’s main surface antigen reveals putative host cell-binding domains.
Gesehen am 19.08.2021